Efficient channel estimation algorithms for cooperative multiple-input multiple-output (MIMO) wireless communication networks - Chiong, Choo Wee Raymond (Curtin University, 2014)
Multiple-input multiple-output (MIMO) relay communication systems have been identified to be one of the promising solutions to high rate wireless communications. In optimizing the MIMO relay networks, the knowledge of channel state information (CSI) is essential. This thesis develops novel channel estimation algorithms for MIMO relay communication networks, considering the amplify-and-forward relaying scheme. The proposed algorithms outperform existing schemes in estimating the CSI of each hop in MIMO relay networks.